Global Norms and Constitutional Law in Indonesia and Pakistan - Muin, Sri Amlinawaty A; Muhdar, Muh. Zulkifli; Mail, Syed Muhammad Huzaif (Faculty of Law Universitas Jenderal Soedirman, 2026)
The interaction between international legal norms and national constitutional law has become increasingly complex, particularly in countries with strong ideological and religious foundations. This study aims to analyze the process of legal adaptation of global norms within the constitutional systems of Indonesia and Pakistan and to identify the social, political, and religious factors that influence their legitimacy and effectiveness. This study employs a comparative legal analysis, focusing on constitutional provisions, statutory regulations, and relevant legal doctrines in Indonesia and Pakistan. The findings reveal that Indonesia adopts a dialogical– inclusive model, in which universal human rights values are contextualized through Pancasila and the principle of Divinity as normative filters, whereas Pakistan adopts a defensive–theological model that positions Sharia as the ultimate boundary of legal supremacy over global norms. Social, political, cultural, and religious values play a significant role in determining the degree of legitimacy and the practical effectiveness of international norms within each domestic context. This study concludes that the effectiveness of implementing international norms largely depends on a state’s ability to balance global commitments with the authenticity of its local values.